Inheritance of resistance to three endemic viral diseases of cowpea in Nigeria - Ogunsola, K.E.; Fatokun, C.; Boukar, O.; Kumar, P. Lava (Informa UK Limited, 2023)
Mosaic diseases, caused by bean common mosaic virus-blackeye cowpea mosaic strain (BCMV-BlCM), southern bean mosaic virus (SBMV), and cucumber mosaic virus (CMV), hamper the productivity of cowpea (Vigna unguiculata (L.) Walp.). Under single or mixed infections, these endemic viruses significantly reduce cowpea yield in sub-Saharan Africa. Planting resistant varieties is the most effective control method. Knowledge of the mode of inheritance of viral resistance is crucial in developing resistant varieties. Inheritance of resistance to BCMV-BlCM, SBMV, and CMV was investigated in two improved cowpea breeding lines. For BCMV-BICM, crosses were made between resistant IT97K-1042-3 (female) and susceptible IT99K-1060 (male); for SBMV, between resistant IT98K-1092-1 (male) and susceptible IT99K-1060 (female); and for CMV, between tolerant IT98K-1092-1 (female) and susceptible IT99K-573-1-1 (male). The F1 progenies were advanced to F2, and some F1 plants were backcrossed to the two parental lines. Reciprocal crosses were made and the 7-day-old seedlings of P1, P2, F1, F2, BCP1, and BCP2 were phenotyped by mechanical inoculation with BCMV-BlCM, SBMV, and CMV under screenhouse conditions. Data on disease incidence and severity were taken at weekly intervals for 5-week post-inoculation. Virus infections were confirmed via antigen-coated plate enzyme-linked immunosorbent assay or reverse transcription-polymerase chain reaction. Chi-square analysis of the genetic segregation indicated that a recessive gene pair in IT97K-1042-3 controlled the inheritance of resistance to BCMV-BlCM. Duplicate dominant genes conditioned the resistance to SBMV and tolerance to CMV in IT98K-1092-1. The backcrosses confirmed the monogenic and digenic inheritance patterns, whereas reciprocal crosses indicated absence of cytoplasmic effects.